A human tragedy? The pace of negative global change exceeds human progress. (April 2019) - Morris, Douglas W
I analyze changes in the demographic profiles and urbanization rates of 201 countries, and assess 69 global indicators of the human condition, in order to evaluate whether the human population is endangering its persistence and future quality of human life (tragedy of the commons). Encouraging changes in age profiles signal a slowing down in human population growth during the Anthropocene while exponential increases in several economic, education, and health indicators support an optimistic outlook for the future of humanity. But rapid growth by a larger number of negative indicators foretell a global human tragedy plagued by long-term increases in pollution, global warming, waning food production and unparalleled declines in biodiversity. Urgent action is required to avoid further collapse of the Earth System.